PENGARUH RASIO KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DIMEDIASI PROFITABILITAS - Ferly, Wiliam; Wijaya, Henryanto (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
In This study aims to determine how the role of capital structure, liquidity, and company size on firm value with profitability as mediation in the health sector industry listed on the Indonesian stock exchange during 2019-2021. the sample that was selected using method of purposive sampling method and valid data as many as 15 companies. data processing techniques using multiple regression analysis assisted by the SmartPLS (Partial Least Square) program. The results showed that capital structure, liquidity and company size had an insignificant effect on firm value. The implication for this research is the need to increase the capital structure, liquidity and size of the company to increase profitability which will increase the value of the company it will bring a good signal to Investors and Stakeholders.